1995
DOI: 10.1039/fd9950100319
|View full text |Cite
|
Sign up to set email alerts
|

Gels from surfactant solutions with densely packed multilamellar vesicles

Abstract: Results on surfactant gels containing densely packed multilamellar vesicles are reported. The gels form spontaneously when the bilayers of L, or L, phases of alkyldimethylaminoxide and cosurfactant are charged up by the addition of ionic surfactant or HCl. The rheological behaviour on addition of excess salt was studied by dynamic rheological measurements for systems with surfactants of different chainlengths. Both the storage modulus, G', and the yield stress, u y , decay with rising salinity. This effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 15 publications
4
40
1
Order By: Relevance
“…In our system, vesicles are easily formed by addition of the cationic surfactant tetradecyltrimethylammonium bromide (TTABr) to the ternary system tetradecyldimethylamineoxide TDMAO/1-hexanol/water ( Figure 2). [25][26][27][28] The total surfactant concentration was always 100 mM, and different phases can be adjusted by variation of the content of the cosurfactant hexanol. The phase sequence in the ternary Schematic quaternary phase diagram of zwitterionic tetradecyldimethylamineoxide (TDMAO), cationic tetradecyltrimethylammonium bromide (TTABr), 1-hexanol, and water at 25°C.…”
Section: Resultsmentioning
confidence: 99%
“…In our system, vesicles are easily formed by addition of the cationic surfactant tetradecyltrimethylammonium bromide (TTABr) to the ternary system tetradecyldimethylamineoxide TDMAO/1-hexanol/water ( Figure 2). [25][26][27][28] The total surfactant concentration was always 100 mM, and different phases can be adjusted by variation of the content of the cosurfactant hexanol. The phase sequence in the ternary Schematic quaternary phase diagram of zwitterionic tetradecyldimethylamineoxide (TDMAO), cationic tetradecyltrimethylammonium bromide (TTABr), 1-hexanol, and water at 25°C.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of vesicles from binary systems or morecomponent systems was observed for nonionic surfactants with hydrophobic chain or sugar surfactants with a small head group, nonionic surfactants with two hydrophobic chains, cationic or anionic surfactants with two long alkyl chains, mixtures of cationic and anionic single-chain surfactants, mixtures of amino acid surfactants or amino acid surfactants at intermediate pH values, perfluoro surfactants with two hydrophobic chains, mixtures of cationic perfluoro and anionic hydrocarbon surfactants, mixtures of cationic/anionic and zwittterionic perflouro surfactants or nonionic perfluoro surfactants, mixtures of surfactants with cosurfactants, and mixtures of perfluoro surfactants with cosurfactants or with perfluoro cosurfactants [23][24][25][26][27][28][29]. Unilamellar vesicles can be prepared also from the lamellar phase by shear [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Such behaviour has for instance been observed for densely packed multilamellar vesicles. [5][6][7] However, it has also been observed that unilamellar vesicles composed of anionic surfactant, cosurfactant, and water can form such a vesicle gel spontaneously. These systems are viscous and according to previous experimental investigations they consist of monodisperse unilamellar small vesicles with a radius of about 15-25 nm.…”
Section: Introductionmentioning
confidence: 99%